Phenotypic Spectrum of CASPR2 and LGI1 Antibodies Associated Neurological Disorders in Children - Jiang, Yan; Tan, Chengbing; Li, Tingsong; Song, Xiaojie; Ma, Jiannan; Yao, Zhengxiong; Hong, Siqi; Li, Xiujuan; Jiang, Li; Luo, Yuanyuan (Frontiers in Pediatrics, 2022)
Objectives: The clinical data of patients with double-positive for leucine-rich glioma-inactivated protein 1 (LGI1) and contactin-associated protein-like 2 (CASPR2) antibodies is limited, particularly for children. This study aimed to investigate and summarize the clinical features and long-term prognosis of children’s LGI1 and CASPR2 antibodies related to neurological disorders. Methods: We collected the clinical data and prognosis of patients with dual positive antibodies of CASPR2 and LGI1, hospitalized in the Department of Neurology, Children’s Hospital of Chongqing Medical University. We summarized the clinical phenotypes of this disorder in children by reviewing the published literature. Results: Two patients presenting with variable neurological symptoms including pain, hypertension, profuse sweating, irritability, and dyssomnia from Children’s Hospital of Chongqing Medical University were enrolled in this study. Together with the two patients, we identified 17 children with dual CASPR2 and LGI1 antibodies, including 12 males and 5 females. At the onset, the median age was 4.1 years (range 1–16, interquartile range 2.5-13.5), with 9 children younger than 5 years and 6 adolescents. Of the 17 patients, 11 were diagnosed with Morvan syndrome, 4 with acquired neuromyotonia,1 with Guillain-Barré syndrome, and 1 with Guillain-Barré syndrome combined with Morvan syndrome. Dysautonomia (14/17, 82.3%), pain (13/17,76.4%), sleep disorders (13/17,76.4%), encephalopathy (12/17, 70.5%), and weight loss (10/17, 58.8%) were the most frequently described symptoms overall. No tumors were identified. Of the 17 patients, 13 received immunotherapy comprising IVIG combination of IVMP during the acute symptomatic phase followed by oral prednisolone to maintain remission(n=7), the combination of IVIG, IVMP, oral prednisolone and methotrexate (n=1), the combination of IVIG, IVMP and mycophenolate mofetil (n=1), the combination of IVIG, IVMP, oral prednisolone and rituximab (n=1), IVIG only (n=2), IVMP only (n=1). Median modified Rankin Scale (mRS) scores in the acute phase were 3 (range 1–4) and improved gradually. Over the follow-up (median 8.6 months, range 1–36 months), 52.9%（9/17）of the patients recovered completely. Conclusion: LGI1 and CASPR2 double-positive antibodies associated with the neurological diseases can occur in children of all ages and involve multiple nervous systems. Morvan syndrome is the most common phenotype of this disorder. The long-term outcomes are mostly favorable upon immunotherapy.